Alzheimer's disease disrupts alpha and beta-band resting-state oscillatory network connectivity. Issue 11 (November 2017) - Koelewijn, Loes; Bompas, Aline; Tales, Andrea; Brookes, Matthew J.; Muthukumaraswamy, Suresh D.; Bayer, Antony; Singh, Krish D.
Highlights: Whole-brain resting-state MEG shows decreased connectivity in AD vs. increases in healthy ageing. Results unique to parietotemporal areas and beta band in AD, highly similar for eyes open and closed. These unbiased results suggest distinct patterns of dysfunction rather than accelerated ageing in AD. Abstract: Objective: Neuroimaging studies in Alzheimer's disease (AD) yield conflicting results due to selective investigation. We conducted a comprehensive magnetoencephalography study of connectivity changes in AD and healthy ageing in the resting-state. Methods: We performed a whole-brain, source-space assessment of oscillatory neural signalling in multiple frequencies comparing AD patients, elderly and young controls. We compared eyes-open and closed group oscillatory envelope activity in networks obtained through temporal independent component analysis, and calculated whole-brain node-based amplitude and phase connectivity. Results: In bilateral parietotemporal areas, oscillatory envelope amplitude increased with healthy ageing, whereas both local amplitude and node-to-global connectivity decreased with AD. AD-related decreases were spatially specific and restricted to the alpha and beta bands. A significant proportion of the variance in areas of peak group difference was explained by cognitive integrity, in addition to group. None of the groups differed in phase connectivity. Results were highly similar for eyes-open and closed resting-state. Conclusions: These results support the disconnection syndrome hypothesis and suggest that AD shows distinct and unique patterns of disrupted neural functioning, rather than accelerated healthy ageing. Significance: Whole-brain assessments show that disrupted regional oscillatory envelope amplitude and connectivity in the alpha and beta bands play a key role in AD.